ANTIBACTERIAL ACTIVITY OF ETHANOL EXTRACT AND VOLATILE OIL OF LAJA GOWAH RHIZOME (ALPINIA MALACCENSIS BURM.F.) ROSCOE) AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI - Sitorus, Panal; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Laja Gowah is one of the herbs that can be used to treat gastrointestinal problems. The aim of this research is characterization, phytochemical screening of simplex and extracts and testing antibacterial activity of ethanol extract and volatile oil of Laja Gowah rhizome against Staphylococcus aureus and Escherichia coli. Methods: Simplex were characterized, phytochemical screening, and extracted by percolation with ethanol 96% as solvent, and volatile oil was extracted by steam distillation and the antibacterial activity against S. aureus and E. coli carried out by agar diffusion method. Results: The characteristic of simplex were 7.50% for water content, water-soluble extract 29.69%, ethanol soluble extract 19.30%, total ash 3.97%, and acid insoluble ash 0.38%. The phytochemical screening of simplex and ethanol extract were showed the presence of alkaloids, flavonoids, glycosides, steroids/triterpenoids, and saponins. Antibacterial activity showed that ethanol extract and essential oils effective as antibacterial against S. aureus and E. coli. Conclusion: Based on the analysis above, that shows that extract and volatile oils rhizome Laja Gowah provide effective activity as anti-bacteria against S. aureus and E. coli. Keywords: Laja Gowah rhizome, Antibacterial, Ethanol extract, Volatile oil, Staphylococcus aureus, Escherichia coli.